Idiopathic pulmonary fibrosis and occupational risk factors - Ranzieri, Silvia; Illica Magrini, Elisa; Mozzoni, Paola; Andreoli, Roberta; Pelà, Giovanna; Bertorelli, Giuseppina; Corradi, Massimo (La Medicina del Lavoro, 2019)
Idiopathic pulmonary fibrosis (IPF) is a rare lung disease of unknown origin that rapidly leads to death. However, the rate of disease progression varies from one individual to another and is still difficult to predict. The prognosis of IPF is poor, with a median survival of three to five years after diagnosis, without curative therapies other than lung transplantation. The factors leading to disease onset and progression are not yet completely known. The current disease paradigm is that sustained alveolar epithelial micro-injury caused by environmental triggers (e.g., cigarette smoke, microaspiration of gastric content, particulate dust, viral infections or lung microbial composition) leads to alveolar damage resulting in fibrosis in genetically susceptible individuals. Numerous epidemiological studies and case reports have shown that occupational factors contribute to the risk of developing IPF. In this perspective, we briefly review the current understanding of the pathophysiology of IPF and the importance of occupational factors in the pathogenesis and prognosis of the disease. Prompt identification and elimination of occult exposure may represent a novel treatment approach in patients with IPF.